EFEITO DE DOIS TRATAMENTOS FISIOTERAPÊUTICOS EM MULHERES IDOSAS COM OSTEOARTROSE DE JOELHO - Almeida, Fabiano de Jesus Furtado (2010)
Osteoarthritis is a pathology of a chronic and degenerative type, affecting the synovial joints as the knee, especially in the elderly. Among the treatment modalities in this disease stand out as the surgical and conservative means through therapy resources such as electrothermotherapy and the kinetic therapy. The general objective of this study was to evaluate the effects of two protocols of physical therapy in elderly women with knee osteoarthritis. The research type is a experimental clinical Trial which were selected for the study 30 female patients aged 61 to 80 years, diagnosed with primary knee OA treated at the Center for Comprehensive Health Care for the Elderly (CAISI Centro de Atenção Integral a Saúde do Idoso) located in São Luís-MA. Group I it was submitted kinetic therapy, and the group II a treated with electro-thermotherapy performing 36 physical therapy for 12 weeks. For the data collection were used summary protocol variables sócio-demographic, Body Mass Index (BMI) at kg/m2, visual analogue scale (VAS) beyond the range of motion (ROM). (The treatments carried out in 2 samples groups showed no statistical differences in BMI, but in pain and there were statistical differences in the ROM groups I and II respectively and that in the var iable (ROM) to the left knee flexion in group II was the only scale that was not statistically significant (p < 0.05). We conclude that both treatment modalities showed effective therapeutic responses with statistically significant differences in groups I and II in pain and ROM (p<0.05).